An expeditious chaos based digital image encryption algorithm - Arun Raj, R.; George, S. N.; Deepthi, P. P. (2012 1st International Conference on Recent Advances in Information Technology, 2012)
Chaos based encryption techniques have been gaining immense attraction for the past few years with a view of enhancing security coupled with reduction in computational complexity. This paper explores the drawbacks of chaotic key based algorithm (CKBA) which was primarily designed for monochrome images. We put forth an improved chaotic key based image encryption algorithm for monochrome and color images. The new algorithm was subjected to the known forms of attack and has been found resistant to the same.